Cannabidiol and its Potential Evidence-Based Psychiatric Benefits – A Critical Review - Dammann, Inga; Rohleder, Cathrin; Leweke, F. Markus (Pharmacopsychiatry, 2024)
The endocannabinoid system shows promise as a novel target for treating psychiatric conditions. Cannabidiol (CBD), a naturally occurring cannabinoid, has been investigated in several psychiatric conditions, with diverse effects and an excellent safety profile compared to standard treatments. Even though the body of evidence from randomised clinical trials is growing, it remains relatively limited in most indications. This review comprises a comprehensive literature search to identify clinical studies on the effects of CBD in psychiatric conditions. The literature search included case studies, case reports, observational studies, and RCTs published in English before July 27, 2023, excluding studies involving nabiximols or cannabis extracts containing CBD and ∆9-tetrahydrocannabinol. Completed studies were considered, and all authors independently assessed relevant publications.Of the 150 articles identified, 54 publications were included, covering the effects of CBD on healthy subjects and various psychiatric conditions, such as schizophrenia, substance use disorders (SUDs), anxiety, post-traumatic stress disorder (PTSD), and autism spectrum disorders. No clinical studies have been published for other potential indications, such as alcohol use disorder, borderline personality disorder, depression, dementia, and attention-deficit/hyperactivity disorder. This critical review highlights that CBD can potentially ameliorate certain psychiatric conditions, including schizophrenia, SUDs, and PTSD. However, more controlled studies and clinical trials, particularly investigating the mid- to long-term use of CBD, are required to conclusively establish its efficacy and safety in treating these conditions. The complex effects of CBD on neural activity patterns, likely by impacting the endocannabinoid system, warrant further research to reveal its therapeutic potential in psychiatry.
Keywords: CBD; cannabinoids; mental illness; psychiatric disorders; therapeutic effects